2016
DOI: 10.3390/s16050753
|View full text |Cite
|
Sign up to set email alerts
|

myBlackBox: Blackbox Mobile Cloud Systems for Personalized Unusual Event Detection

Abstract: We demonstrate the feasibility of constructing a novel and practical real-world mobile cloud system, called myBlackBox, that efficiently fuses multimodal smartphone sensor data to identify and log unusual personal events in mobile users’ daily lives. The system incorporates a hybrid architectural design that combines unsupervised classification of audio, accelerometer and location data with supervised joint fusion classification to achieve high accuracy, customization, convenience and scalability. We show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another finding suggests using of smartphone sensors joint fusion network by implementing and evaluating end-to-end systems of android smartphones with cloud servers (Ahn & Han 2016). Mentioning this find suggests using hybrid architectural design of unused smartphone sensors to achieve high accuracy, customization and convenience (Ahn & Han 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another finding suggests using of smartphone sensors joint fusion network by implementing and evaluating end-to-end systems of android smartphones with cloud servers (Ahn & Han 2016). Mentioning this find suggests using hybrid architectural design of unused smartphone sensors to achieve high accuracy, customization and convenience (Ahn & Han 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus we have possible ways to stop those kinds of incidents if we somehow make this system practical. As I have already stated, the CIFDR is in its high stage of development and going several associated challenges are being solved with the help of researchers currently working in this field through different means and medium of integrated sensors (Ahn & Han 2016). This system will provide us the real data, and our future vehicles, either aerial or terrestrial vehicles will be more safety-bearing standards than the current basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusing various algorithms results in an efficiency that is higher than the accuracy of each algorithm alone, and the study conducted by Ahn et al [25] achieved a stable and satisfactory performance for a bagging-based reinforcement algorithm. Furthermore, Delgado et al [26] demonstrated that the random forest algorithm exhibited the best performance among bagging-based algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, the locations are embedded into the photos for remembrance. Then, these location-embedded data will be published in the mobile cloud automatically [1,2,6], such as iCloud, Samsung cloud, etc. These location-embedded data bring great convenience for cloud service providers (CSP) to provide location-based services (LBS) for users [3,7].…”
Section: Introductionmentioning
confidence: 99%